2011
DOI: 10.1111/j.1743-6109.2011.02416.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type 5 Expression in Human and Rat Lower Urinary Tract Tissues and the Effect of Tadalafil on Prostate Gland Oxygenation in Spontaneously Hypertensive Rats

Abstract: Introduction In humans, prostate phosphodiesterase type 5 inhibitors (PDE5) expression was prominently localized in the endothelial and smooth muscle cells of the vascular bed, suggesting a possible action of PDE5 inhibitors (PDE5i) on prostate blood flow. Aim To investigate PDE5 expression in human and rat lower urinary tract (LUT) tissues, including vasculature, and determine the effects of PDE5 inhibition with tadalafil on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 56 publications
9
119
0
4
Order By: Relevance
“…[10][11][12] PDE5 inhibitors acts by upregulation of the NO/cGMP activity. Preclinical studies reported partial reversal of nor-epinephrine-and endothelin-1-reduced prostatic tissue contraction 13 and an anti-proliferative effect on cultured prostate and bladder smooth muscle cells 14 . These mechanisms may decrease smooth muscle tension in the prostatic stroma and capsule and attenuate cellular proliferation associated with prostate/bladder hypertrophy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] PDE5 inhibitors acts by upregulation of the NO/cGMP activity. Preclinical studies reported partial reversal of nor-epinephrine-and endothelin-1-reduced prostatic tissue contraction 13 and an anti-proliferative effect on cultured prostate and bladder smooth muscle cells 14 . These mechanisms may decrease smooth muscle tension in the prostatic stroma and capsule and attenuate cellular proliferation associated with prostate/bladder hypertrophy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the possible mechanisms include relaxation of smooth muscle tones in the lower urinary tract caused by increased cyclic guanosine monophosphate, inhibition of local inflammatory processes, and improvement in blood flow and oxygenation to the lower urinary tract. (36)(37)(38) • Efficacy: Most studies demonstrate improvements in IPSS and QOL, but no significant improvement in Qmax. (39) Only tadalafil 5 mg daily has been approved for use in male LUTS by the US Food and Drug Administration and Health Sciences Authority, Singapore.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%
“…Preclinical studies reported partial reversal of nor-epinephrine-and endothelin-1-reduced prostatic tissue contraction 13 and an anti-proliferative effect on cultured prostate and bladder smooth muscle cells 14 . As a result there is decrease in smooth muscle tension in the prostatic stroma and capsule and also attenuate cellular proliferation associated with prostate/bladder neck hypertrophy respectively.…”
Section: Discussionmentioning
confidence: 99%